Challenges of Parenting in an Urban Setting - Hendriati, Agustina; Okvitawanli, Ayu (Psychological Research on Urban Society, 2019)
Child development is affected by the physical and socio-cultural environment, both directly and through parental behavior. This paper examines the characteristics of urban environments in comparison with rural areas, along with their implications for parenting practices. Challenges facing urban parents are discussed, including time scarcity, failure to impart moral values, work/life imbalance, and the lack of emotional bonding. The case of Jakarta as a mega city has been chosen to illustrate these challenges. The paper also suggests some solutions be adopted from experience in more developed countries.